Comparative study of physicochemical and functional properties of pan and microwave cooked underutilized millets (proso and little). (June 2020) - Kumar, Simmi Ranjan; Sadiq, Muhammad Bilal; Anal, Anil Kumar
Abstract: Physiochemical properties such as colour, water absorption index (WAI), water solubility index (WSI) bulk density and the functional properties such as water absorption capacity (WAC), oil absorption capacity, least gelation concentration, foaming capacity, foaming stability, pasting properties, in vitro starch digestibility and microstructure of underutilized millet (proso and little) flours were evaluated. The millets flour exhibited considerable amounts of carbohydrates (78.37–81.69 g/100 g) and proteins (4.48–10.32 g/100 g). Microwave cooked little millet (MWLM) (10.32 g/100 g), and pan-cooked proso millet (PCPM) (9.07 g/100 g) flour contained a significantly higher amount of proteins than the raw millets. WAI (4.48 g/g) and WSI(4.17 g/g) of MWLM were significantly higher than the other flours. The functional properties of MWPM such as WAC (3.23 g/g) and OAC (0.90 g/g) were higher than the other flour samples. The microstructure of flour samples revealed that the starch granules of raw flours were smooth, oval and granular structure whereas cooked flours have deshaped starch granules. The under-utilized millets can further be used as an essential source of nutrients and functional ingredients in various food formulations, including for functional foods. Highlights: Proso millet and little millet are gluten-free underutilized millets. Underutilized millets have potential for incorporation in functional foods. Underutilized millets flours exhibit better nutritional and functional properties after cooking treatments.